Bereavement and mental health issues for institutionalized children - Ali, Asif; Shaffie, Fuziah (UUM Press, 2021)
The loss of a caregiver or loved one is a tragic moment, which can have psychosocial impact on a child. Children inside institutions either in foster or residential care are prevalence to the experience of neglect and parental loss bereavement. Bereavement endures a variety of factors that influence negatively on child mental health. The purpose of this concept paper is to explain noteworthy contributions with regards to information on bereavement among children and their psychosocial problems in institutions and residential cares. The attachment theory is significant to explain the association of bereavement and institutions, which supported the evidence that bereavement among vulnerable population inside institution, are at high risk of social deterioration. The theory implies a cause-effect relationship between early attachments. Children are potentially psychologically affected by any traumatic events, which caused them to experience prolong mental developmental delay that are associated with different psychological disorders. Institutionalized children can easily become victim of their psychosocial inability to defend themselves from ruthless violence. Research had examined the differentiating factors of certain symptoms in normal grief and bereavement within the context of depressive disorders, including self-guiltiness, death thoughts, maltreatment, and worthlessness. Experiences of bereavement may occur over the loss, which then shifted to transient withdrawal. Parental loss is one of the most extreme social deprivations that a child can experience Therefore responses to parental loss may be age-specific, related to temperament and to culture. The literature indicated that bereavement in institutional settings has the potential to cause significant risks of mental health with the most prevalent impact related to psychological issues. To cope with the consequences of child maltreatment, prolonged effective interventions should be encouraged. Noteworthy, studies related to bereavement and stress to explain the psychological health issues of children due to parental loss in institutional care are limited, especially within the context of developing countries.